Implementasi Larangan Illegal Fishing (Racun dan Setrum Ikan) di Kecamatan Sanga-Sanga - Muhammad Rio Rinaldi; Fitriyana Fitriyana (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This study aimed to analyze the implementation of policies prohibiting illegal fishing practices involving the use of explosives, poisons, and electric shock devices in Sanga-Sanga District, Kutai Kartanegara Regency. Although regulations and extension activities related to the prohibition have been established, illegal fishing practices continue to occur as of 2025. The findings reveal that some fishermen still use poison and electric shock due to economic reasons and the perception that these methods yield greater catches. However, such actions cause losses to other fishermen by reducing the quality of the catch and damaging the aquatic ecosystem. The community is aware of these violations but is reluctant to report them due to fear of threats from the perpetrators. Efforts by fisheries extension officers to establish community-based surveillance groups (Pokmaswas) have not been optimal due to low public participation. Collaboration between provincial fisheries supervisors and the local marine police (Polairud) has resulted in joint patrols that successfully apprehended two perpetrators of illegal fishing, yet law enforcement has not produced a deterrent effect. Moreover, the program to replace destructive fishing gear with environmentally friendly alternatives for fishermen willing to transition has not been realized due to budget constraints. Based on these findings, it is necessary to strengthen integrated surveillance, provide legal protection for whistleblowers, accelerate the implementation of sustainable fishing gear programs, and enhance public awareness of legal and ecological issues.